Visualisation of contemporary public art - Vincenzo Lombardo; Nadia Guardini; Alessandro Olivero (Mimesis Journal, 2014)
This paper deals with the visualization phase of Invisibilia Project. The visualization phase takes as input the ontological representation and provides as output a 3d layout that takes into account the relevant elements for the contemporary art. In particular, the visualization phase has addressed the visualization of contemporary public art and the information related to the individual artworks. The design layout, being referred to urban and architectural settings, relies on 3d graphics and splits the items visualized into two categories: the artwork itself, which is represented with realistic, photographic features, and the setting items, which are represented with icons. The software architecture has explored two possible implementations, with an open source library and a proprietary environment, respectively. The paper ends with a discussion of the results.